Evaluation of Antibiotic Planning in the UNS Hospital Pharmacy Installation in 2021 - Zulpadly, Muhammad Fiqri; Syarofina, Nisa’ (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Planning is a drug selection activity in determining the type and amount of drug to increase efficiency, periodic and rational use of drugs, as well as obtaining an estimate of the amount of drug needed. Antibiotics are drugs that are often used and absorb many funds, so effective planning needs to be done so that inventory can be under control. This study aims to obtain a drug classification for antibiotics with the ABC analysis method to facilitate the control of antibiotic drugs in the Hospital Pharmacy Installation UNS. This research includes non-experimental research with descriptive analysis using quantitative and qualitative data. Quantitative data was obtained from prescriptions containing antibiotic drugs during 2021, and qualitative data regarding planning processes and systems procurement of drugs was obtained based on interviews with the Hospital Pharmacy Installation UNS warehouse coordinator. In this study, the results obtained were that of 100 drug items antibiotics, class A consists of three drug items (22.2%), class B consists of 10 drug items (22.47%), and class C consists of 57 drug items (55.33%). Class A has a planned budget proportion of IDR 413,106,692 (66.73%) of the total budget: IDR 619,100,298; Class B has a planned budget proportion of IDR 140,848,487 (22.75%); Class C has a planned budget proportion of IDR 65,145,119 (10.52%). Using the ABC method can simplify planning and procuring drugs and affect the proportion of the budget for drug procurement in hospitals.